Pengetahuan, Sikap dan Perilaku DAGUSIBU Obat pada Kader PKK - Nurul Mutmainah; Putri Nabila Miftahul Jannah; Zuhroh Tustika Vieda (Pharmacon: Jurnal Farmasi Indonesia, 2022)
DAGUSIBU teaches how to administer medications properly. Errors in drug management can be influenced by a lack of knowledge. Knowledge is an important foundation that can influence a person's attitude and behavior. This study aims to determine the relationship between the level of knowledge on attitudes and behavior related to  DAGUSIBU among Kader PKK. This research is an observational study with a cross-sectional approach. The population in this study was Kader PKK in Kalurahan Kampung Baru, KecamatanPasar Kliwon, Kota Surakarta and Kalurahan Sendangsari, Kecamatan Pengasih, Kabupaten Kulon Progo Regency. Sampling was done by purposive sampling technique. The research measuring instrument used a questionnaire consisting of 4 parts, namely informed consent, questions about knowledge (20 items), questions about attitudes (10 items), and questions about behavior (10 items). Multivariate analysis in this study was carried out using multiple linear regression analysis methods. The results of the study on 198 people showed that 101 people (51%) had a good level of knowledge. 138 people (69.7%) had a good attitude and in the behavioral aspect of the drug DAGUSIBU it was found that 155 people (78.3%) had good practicals. From the results of linear regression analysis, the sig. 0.000, this shows that there is a relationship between the level of knowledge of DAGUSIBU   attitudes and practicality among Kader PKK. The level of knowledge affects the attitude of 19.3% while the level of knowledge influences the practical of 17.8%